2013
DOI: 10.1158/1078-0432.ccr-13-0836
|View full text |Cite
|
Sign up to set email alerts
|

A Clinical Model for Identifying Radiosensitive Tumor Genotypes in Non–Small Cell Lung Cancer

Abstract: Purpose: Non-small cell lung cancer (NSCLC) includes a spectrum of radiosensitive and radioresistant tumors. However, little is known about the molecular determinants of cellular radiation responses. We examined clinical outcomes after gamma knife radiotherapy for NSCLC intracranial metastases to evaluate the use of this model for determining radiosensitive tumor genotypes.Experimental Design: Between 2005 and 2012, 239 patients with NSCLC were enrolled in a prospective gamma knife data repository. Molecular p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
57
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(69 citation statements)
references
References 54 publications
(61 reference statements)
7
57
1
1
Order By: Relevance
“…The positive prognostic role of EGFR mutations is likely due to the higher intracranial response rates observed with EGFR TKIs, a better extra-cranial disease control and, finally, an increased sensitivity to loco-regional treatments, such as WBRT and SRS [3336]. …”
Section: Discussionmentioning
confidence: 99%
“…The positive prognostic role of EGFR mutations is likely due to the higher intracranial response rates observed with EGFR TKIs, a better extra-cranial disease control and, finally, an increased sensitivity to loco-regional treatments, such as WBRT and SRS [3336]. …”
Section: Discussionmentioning
confidence: 99%
“…Several studies showed that the radiosensitivity of brain metastases is associated with the mutation status of epidermal growth factor receptor (EGFR) [25-27]. Compared to patients with the wild-type, those with activating EGFR mutations had higher response rates and better survival following WBRT (54% VS. 24%, P  = 0.045; 17.3 months VS .…”
Section: Discussionmentioning
confidence: 99%
“…In HNSCC, for example, EGFR overexpression is a marker of poorer outcomes (57)(58)(59). However, in lung adenocarcinoma, EGFR mutant cells are 500-1000 fold more sensitive to radiation than wild-type cells in vitro (60) and retrospective clinical data show that patients with EGFR mutant tumors demonstrated significantly better response rates compared to patients whose tumors lacked mutations in EGFR (61,62). It remains unclear whether the demonstrated sensitivity to radiation in EGFR mutant patients is causative or correlative.…”
Section: Erbb Receptor Familymentioning
confidence: 99%